Encapsulation of oryzanol-rich rice bran oil using carrageenan. Issue 1 (April 2021) - Fadilah,; Distantina, Sperisa; Susanti, Ari Diana; Damara, Liginia Gustin Ayu; Mawarni, Grace Hana
Abstract: Experiments have been carried out to encapsulate rice bran oil using carrageenan. Two methods have been tried. In the first method, the chitosan-carrageenan polymer solution was dropped into the NaOH-ethanolate solution. The solid formed is filtered and immersed in a 6% glutaraldehyde solution, then filtered and dried. The resulting solid is clustered and not form granules. In the second method, a solution called A in the form of oil emulsion in carrageenan solution is dropped into chitosan solution and then heated to 70°C. Glutaraldehyde is added to the solution, and the cross-linking process is continued for 3 hours. The solid is filtered and washed with water then with n-hexane. The resulting solid is washed with ethanol and then dried. Experiments result with variation in the amount of carrageenan showed the best results when using 0.3 g carrageenan and 0.5 mL of oil.